Estudo do pH e atividade antimicrobiana sobre Enterococcus faecalis de medicação intracanal à base de hidróxido de cálcio associada ao óleo de melaleuca, clorexidina ou farnesol - Vasconcelos, Rodrigo Arruda [UNESP] (2016)
Intracanal medications (ICM) are used to complement desinfection of the root canal system. The association of antimicrobials to calcium hydroxide aims to improve its action. The ICM (Chapter 1) calcium hydroxide (CH)/tea tree oil (TTO) 4.5%/polyethylene glycol 400 (PL), CH/TTO 9%/PL, CH/chlorhexidine (CHX) 0.4%/PL e CH/PL (Chapter 2) CH/farnesol (FAR) 4.5%/PL, CH/FAR 9%/PL and HC/PL were analysed. Direct contact test against E. faecalis planktonic cells (Chapters 1 and 2) was performed by using suspension of ICM. Direct contact test on biofilm (Chapter 2) was performed on bovine dentin blocks (5mm x 5mm x 0.7mm) with E. faecalis biofilms induced by 15 days and contact with the suspensions of ICM for 6 hours. Antibacterial effectiveness was evaluated in root canals of extracted human teeth (Chapters 1 e 2). Standardized single-rooted teeth with 15mm were prepared up to #40/.04 MTwo and contaminated with E. faecalis for 21 days. As ICM were kept within the root canals for 7 days. The first sample (S1) was performed after contamination, S2 immediately after the ICM removal and S3 7 days after the ICM removal.It was performed UFCmL-1 count. pH was evaluated after filling the polyethylene tubes (Chapter 1 and 2) with the ICM for 12 hours, 1, 3, 7, 14, 21 and 28 days. The diffusion of hydroxyl ions through the bovine dentin (Chapters 1 and 2) was evaluated after filling root canals of bovine teeth after 1, 3, 7, 14, 21, 28 and 60 days. Data was statistically analyzed using ANOVA and Tukey’s test (p<0,05). Results: (Chapter 1) all ICM were effective against planktonic cells. ICM containing TTO and CHX were more effective compared to CH/PL. The association of TTO and CHX 0.4% to HC not affect the ionization capacity of ICM. (Chapter 2) The addition of FAR did not change the alkalizing ability of the CH. All ICM were effective against planktonic cells. The ICM containing FAR were more effective against E. faecalis than CH within root canals. Conclusions: (Chapter 1) The addition of TTO 4.5 and 9%, as well as CHX 0.4% increased the HC antimicrobial activity without modifying the release of hydroxyl ions. (Chapter 2) The addition of Farnesol 4.5 and 9% enhances the antimicrobial activity of calcium hydroxide without interfering with the release of hydroxyl ions.